Access and utilization of health services by migrant domestic helpers in Cyprus: the role of the employer. Issue 1 (4th March 2019) - Kantaris, Marios; Theodorou, Mamas; Kaitelidou, Daphne
Abstract : Purpose: The dominant role of the employer regarding the access and use of healthcare services by migrant domestic helpers (MDH) often has a negative impact on healthcare provision for migrants in Cyprus. Research relating to the perceptions of MDH employers remains scarce. The purpose of this paper is to investigate the role of employers on the access and use of healthcare services by their MDH. Design/methodology/approach: Three studies were carried out using semi-structured interviews with MDH ( n =13) and employers of MDH ( n =12) and structured questionnaires with MDH ( n =625). Content analysis for qualitative findings was carried out using QSR Nvivo 10 and for quantitative using Statistical Package for Social Sciences version 17. Findings: Findings provide information about migrant health needs from different views leading to improved documentation via multiple triangulation. Employers play a key gatekeeping role but are not in position to provide sufficient information and guidance to their MDH. MDH reported a need for health services which was not met (18 percent), attributing this to their employers not granting them permission. Originality/value: The role of the employer is critical and has an impact on the quality of care provided to this migrant group. The involvement of the employer in MDH health matters functions as a barrier. A significant gap exists between employers and MDH regarding the health needs of the latter.